Mitigating climate change impacts on health: a comparative analysis of strategies in Saudi Arabia and Lebanon - Al Khatib, Alissar; Alsaleh, Bshayer; Almari, Mohammed; Hassanein, Salwa; Al Hakawati, Nawal (Frontiers in Public Health, 2025)
IntroductionHuman activities are now adding rapidly more greenhouse gases to the atmosphere causing global warming which is one aspect of climate change, the greatest threat to public health. Therefore, this study aims to compare the health impacts of climate change on Saudi Arabia and Lebanon, and assessing their adaptation strategies in addressing climate change challenges.MethodologyThis study is a descriptive Comparative Analysis, this was performed by analyzing the available data on climate-related health outcomes: food insecurity, emergence of infectious disease and car accidents and by comparing trends and percentages between the two countries.Results and discussionSaudi Arabia and Lebanon has markable high CO2 emission, which negatively affect the health of people such as Food insecurity (in KSA: The estimated loss over the periods in all the crops ranges from 7 to 25%, in Lebanon: There is a decreased the growth of coveted crops, and increased the growth of weeds and pests), Road traffic accidents (approximately 1.3 million people die as a result of road traffic accidents and 20–50 million people suffer from other injuries.), and Emergence of infectious diseases (in KSA: an increase in 1°C of temperature caused a significant increase (15–25%) in malaria incidence, and increase in risk of food- borne diseases, in Lebanon: There is a vulnerability to the rise in food-borne and vector-borne diseases.). Forecasting the future for both countries reveal to a definite climate change occurring. Further actions could be implemented to overcome the negative health outcomes according to each country. Agriculture and Food Security, Use of renewable energy, and Awareness Campaigns on climate change and health are measures that could be implemented to face the outcomes of climate change. Interestingly, there are some organizations funding initiatives and activities in raising awareness of climate change.ConclusionNumerous sectors are impacted by climate change, which is a serious issue that requires immediate action. It has a substantial influence on many different sectors and leads to food instability, agricultural issues, an increase in infectious disease transmission, and a rise in traffic accidents. These elements require particular care, and appropriate action should be done to eliminate them.